Respuesta :

Answer:

f = 1, w = 4

Step-by-step explanation:

Given the 2 equations

5w = 23 - 3f → (1)

4f = 12 - 2w (add 2w to both sides )

2w + 4f = 12 ( subtract 4f from both sides )

2w = 12 - 4f → (2)

Multiplying (1) by 4 and (2) by - 3 and adding the result will eliminate f

20w = 92 - 12f → (3)

- 6w = - 36 + 12f → (4)

Add (3) and (4) term by term to eliminate f

14w = 56 ( divide both sides by 14 )

w = 4

Substitute w = 4 into either of the 2 equations and solve for f

Substituting into (1)

5(4) = 23 - 3f

20 = 23 - 3f ( subtract 23 from both sides )

- 3 = 3f ( divide both sides by - 3 )

1 = f

Answer:

Step-by-step explanation:

Ver imagen tulasi1415333
ACCESS MORE